2006
DOI: 10.1590/s0104-66322006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Photodecomposition of hydrogen peroxide in highly saline aqueous medium

Abstract: -The photodecomposition of hydrogen peroxide was performed in highly saline aqueous medium (60 g.L -1 of NaCl). The Fe 3+ /H 2 O 2 /NaCl/UV system was tested at temperatures from 20 to 50 o C, while the intervals of concentration of Fe 3+ and H 2 O 2 were 1 to 2.5 mM and 230 to 630 mM, respectively. It is known from the literature that chloride is an inhibitor of the oxidation of organic compound in aqueous medium, but this effect has not been observed to be expressive for hydrogen peroxide. Despite this resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…But even during daytime these radicals and their recombination products coexist due to the cycling between q Cl, q OH, Cl 2 , HOCl and H 2 O 2 . This cycling is activated by sunlight photolysis and radical recombination reactions (Luna et al, 2006;von Glasow, 2000).…”
Section: Oxidation Of Methane and Other Ghgsmentioning
confidence: 99%
“…But even during daytime these radicals and their recombination products coexist due to the cycling between q Cl, q OH, Cl 2 , HOCl and H 2 O 2 . This cycling is activated by sunlight photolysis and radical recombination reactions (Luna et al, 2006;von Glasow, 2000).…”
Section: Oxidation Of Methane and Other Ghgsmentioning
confidence: 99%
“…Several scientific investigations into the photochemical oxidation of phenol derivatives such as the herbicide 2,4-D (2,4-dichlorophenoxyacetic acid) have been published (Alfano et al, 2001;Boval and Smith, 1973;Cabrera et al, 1997;Lee et al, 2003;Luna et al, 2006;Martín et al, 1997;Piera et al, 2000;Sanches et al, 1996;Wang andLemley, 2001 andPignatello, 1992). The increasing interest in 2,4-D can be attributed to its large scale production, and also because this herbicide and its precursors, phenol and 2,4-dichlorophenol (2,4-DCP), are considered hazardous organic pollutants with LD50 between 100 and 500 mg/kg (Krijgsheld and Gen, 1986;Zeep et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Pignatello (1992) conducted experiments involving the thermal and photochemical decomposition of 2,4-D and H 2 O 2 in the presence and absence of Cl À and found that chloride reacts with HO in competition with 2,4-D. It has also been observed that chloride has only a minor effect on H 2 O 2 photodecomposition (Luna et al, 2006;Pignatello, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, more efficient methods for destroying organic pollutants from wastewaters at lab and pilot plant scale are being developed from the advanced oxidation technology (Nogueira et al, 2008;Muhammad et al, 2008;Luna et al, 2006;Silva et al, 2002;Tôrres et al, 2007;Santos et al, 2006;Azevedo et al, 2009). The most suitable materials and optimized experimental conditions are established in most photocatalytic and catalytic techniques for different reactor configurations.…”
Section: Discussionmentioning
confidence: 99%